Altered left ventricular contraction pattern during right ventricular pacing: assessment using real-time three-dimensional echocardiography. - WOLBER T; HAEGELI L; HUERLIMANN D; BRUNCKHORST C; LÜSCHER TF; DURU F (Pacing & Clinical Electrophysiology, 2011)
Chronic right ventricular apical (RVA) pacing has been associated with increased risk of heart failure and adverse outcome. The acute effects of RVA pacing on three-dimensional (3D) ventricular function and mechanical dyssynchrony are not well known. We performed a real-time 3D echocardiographic (RT3DE) study to assess global and regional left ventricular function during RVA pacing. Twenty-six patients with implanted cardiac devices and normal intrinsic atrioventricular conduction were included in the study. RT3DE was performed during intrinsic sinus rhythm and during RVA pacing. Quantification of global and regional left ventricular function was performed offline by time-volume analysis of 16 myocardial segments. Time to reach minimum regional volume was calculated for each segment as a percentage of the cardiac cycle. The systolic dyssynchrony index (SDI) was defined as the standard deviation of these time periods. Longitudinal function was assessed by time-volume analysis of apical, midventricular, and basal segments. During RVA pacing, a reversed apical-to-basal longitudinal contraction sequence was observed in 58% of all patients. RVA pacing was associated with increased left ventricular (LV) dyssynchrony (SDI increase from 4.4 ± 2.2% to 6.3 ± 2.4%, P = 0.001) and reduced LV ejection fraction (decrease from 53 ± 13% to 47 ± 14%, P = 0.05). RT3DE assessment of LV function provides evidence that pacing from the RVA results in acute alterations in LV contraction sequence and increased LV dyssynchrony. Further studies are warranted to assess the potential of RT3DE to identify patients who might be at increased risk of pacing-induced heart failure or who might benefit from alternate-site or multisite pacing. (PACE 2011; 76-81)